Primary percutaneous coronary intervention in CAD patients: A comparison of major adverse cardiovascular events of second- and third-generation drug-eluting stents - Bibi, Salma; Khan, Amjad; Khan, Amer Hayat; Khan, Muhammad Niaz; Mushtaq, Saima; Rashid, Sheikh Abdur (Frontiers in Pharmacology, 2022)
Background: Biodegradable polymer (BP) drug eluting stents (DES) have been introduced as a novel solution to the problems of durable polymer (DP) stents. In Pakistan, very few studies are available for treatment intervention post-primary percutaneous coronary intervention (PPCI). Our study will compare the major adverse cardiovascular events (MACE) and their predictors in coronary artery disease (CAD) patients undergoing PPCI with second or third generation DES. Methodology: An observational, cohort study was carried out on CAD patients undergoing PPCI with either second (Xience Prime, Xience Xpedition) or third generation (Biomatrix Neoflex, Biomatrix Alpha) DES. MACE were assessed after one year of PPCI procedure. Results: 341 patients were recruited in the study after screening as per inclusion/exclusion criteria (167 in second-generation and 174 in third generation group). In our study population, male (86.2%) patients were more than females. MACE were reported in 4.19% patients after one year duration, percentage of MACE was more in second generation DES group (4.77%) than third generation (3.44%); however, statistical analysis has not found any significant difference (P= 0.534). The rate of myocardial infarction (1.19% vs. 0.57%) and stent thrombosis (1.8% vs. 1.15%) was more in second geeration DES group. Restenosis (1.19% vs 1.15%) and cardiac death (0.59% vs 0.57%) was almost same in both groups. A significant association was found between MACE and diabetes mellitus (P= 0.025), hypertension (P= 0.035), smoking (P= 0.008) and family history of CAD (P= 0.018). Conclusion: BP-third-generation Biomatrix and DP-second-generation Xience DES have comparable clinical outcomes. However, longer follow-up studies are required for convincing results.